2008
DOI: 10.1002/mus.21084
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diathermy on muscle temperature, electromyography, and mechanomyography

Abstract: This study examined the effects of pulsed shortwave diathermy on intramuscular temperature, surface electromyography (EMG), and mechanomyography (MMG) of the vastus lateralis. Thirty-five men were assigned to diathermy (n = 13), sham-diathermy (n = 12), or control (n = 10) groups. Each subject performed isometric maximal voluntary contractions (MVCs) and incremental ramp contractions (10%-90% MVC) before and after treatment. Torque, intramuscular temperature, EMG, and MMG were recorded. Temperature for the dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 35 publications
4
17
0
Order By: Relevance
“…Five studies focused on patients with spinal cord injuries [109][110][111][112][113], two on patients with Parkinson's disease [27,114] and with chronic obstructive pulmonary disease [115,116], one study on patients with myopathy [117]. The other six studies were conducted on healthy, able-body participants [20,28,30,[118][119][120].…”
Section: Mmg In the Rehabilitation Fieldmentioning
confidence: 98%
See 2 more Smart Citations
“…Five studies focused on patients with spinal cord injuries [109][110][111][112][113], two on patients with Parkinson's disease [27,114] and with chronic obstructive pulmonary disease [115,116], one study on patients with myopathy [117]. The other six studies were conducted on healthy, able-body participants [20,28,30,[118][119][120].…”
Section: Mmg In the Rehabilitation Fieldmentioning
confidence: 98%
“…Mitchell et al [20] examined the effects of pulsed shortwave diathermy on intramuscular temperature and MMG of the vastus lateralis muscle. They found that intramuscular temperature, as well MMG amplitude and MF increased during the MVC with the greatest increases observed for the diathermy group.…”
Section: Mmg In the Rehabilitation Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…This period was strictly adhered to and the individuals were then submitted to additional maximal contraction of the biceps brachii on both arms, but with the prior administration of microwave diathermy (heat) for 16 min on the dominant arm. The expected circulatory effects caused by diathermy initiate 12e15 min into treatment (Goats, 1999;Low and Reed, 1994;Mitchell et al, 2008). Although previous studies report that the greatest increase in temperature provided by diathermy occurs 20 min into treatment (Draper et al, 1999;Garrett et al, 2000;Mitchell et al, 2008) and this is the most cited time in the literature (Mitchell et al, 2008;Saga et al, 2008;Nosaka et al, 2007), a time of 16 min was established in the present study, as this was the minimal time required to trigger therapeutic physiological effects.…”
Section: Methodsmentioning
confidence: 98%
“…While some studies did not retrieve any significant alteration in neuromuscular function due to changes in muscle temperature (Tm) (Mitchell et al, 2008;Mito et al, 2007), the manipulation of Tm has been found to modify significantly neuromuscular activation during both voluntary (Cheung and Sleivert, 2004;de Ruiter et al, 1999;Dewhurst et al, 2010;Holewijn and Heus, 1992;Petrofsky and Laymon, 2005;Petrofsky and Lind, 1980;Racinais and Oksa, 2010;Ranatunga et al, 1987) and electrically-evoked contractions (Bigland-Ritchie et al, 1992;de Ruiter et al, 1999;Hopf and Maurer, 1990;Racinais and Oksa, 2010;Ranatunga et al, 1987). In particular, despite no changes have been reported with high Tm (Tm H ) (Cheung and Sleivert, 2004;Dewhurst et al, 2010;Holewijn and Heus, 1992;Petrofsky and Laymon, 2005), a significant decrease in force generating capacity (Bigland-Ritchie et al, 1992;Cheung and Sleivert, 2004;de Ruiter et al, 1999;Holewijn and Heus, 1992;Hopf and Maurer, 1990;Petrofsky and Laymon, 2005;Ranatunga et al, 1987), in surface electromyogram (EMG) frequency content (Dewhurst et al, 2010;Holewijn and Heus, 1992;Petrofsky and Lind, 1980;Ranatunga et al, 1987) and in mean fiber conduction velocity (CV) (Merletti et al, 1984;Mucke and Heuer, 1989) have been previously described with low Tm (Tm L ).…”
Section: Introductionmentioning
confidence: 98%